PENGEMBANGAN KLASTER INDUSTRI PERKAPALAN UNTUK MENINGKATKAN DAYA SAING INDUSTRI PERKAPALAN NASIONAL = THE DEVELOPMENT OF SHIPPING INDUSTRY CLUSTERS FOR INCREASING COMPETITIVENESS OF NATIONAL SHIPPING INDUSTRY - Habibie, Sudirman; Gumelar, M. Dikdik; Sitorus, Rudy (BPPT, 2015)
Abstract Government effort to develop marine potency in Indonesia constitutes as a breaktrough program that has been waiting for decade. Considering broad of sea region about 70% from total of Indonesian region, it is reasonable that the future of Indonesia economy is in the sea. One of potencial sector that can be developed is sea transportation sector as sea vehicle (ship). A number of national commerce ships was developed significantly more than 100% from about 6,000 units in 2006 to about 12,500 units in 2013. In the future, this may increase faster because of Government policy to strengthen the development of marine economy, to develop marine axis and to develop sea toll. These programes have to be supported by developing shipping industries, in which they can build new ships and for maintenance. To speed up the increase of roll of shipping industries, the cluster of shipping industry may be needed to be developed in some regions. This cluster consists of several related industries that are core industries, supporting industries and related industries. The development of ship industry clusters have to consider potency of region, region development program, value chain industries, and human resources. Government has to give special policies such as fiscal policy and incentive to develop priority industries and ship industry cluster. Abstrak Usaha pemerintah dalam mengembangkan potensi maritim Indonesia, merupakan suatu program terobosan yang telah ditunggu-tunggu sejak lama. MemperhatikaN luas wilayah laut Indonesia yang meliputi +70% luas wilayah nusantara, maka beralasan bahwa masa depan ekonomi Indonesia ada di laut. Salah satu sektor yang sangat strategis dalam pengembangannya adalah sektor transportasi laut yaitu pengembangan industri perkapalan. Jumlah kapal niaga nasional berkembang dari +6.000 unit pada tahun 2005 dan menjadi +12.500 unit tahun 2013 meningkat lebih dari 100%. Hal ini akan meningkat lebih pesat lagi dengan adanya kebijakan pemerintah memperkuat ekonomi maritim, poros maritim dan tol laut. Peningkatan ini harus didukung juga oleh peningkatan industri galangan kapal baik itu untuk keperluan pembangunan kapal baru maupun untuk perawatan dan perbaikan kapal-kapal yang ada. Untuk mempercepat peningkatan peran industri galangan kapal, maka diperlukan pembentukan klaster industri kapal dalam beberapa wilayah. Klaster ini merupakan sekumpulan industri yang terkait baik berupa industri inti, industri pendukung dan industri terkait. Pembentukan klaster industri perkapalan harus mempertimbangkan potensi wilayah, program pengembangan kawasan, rantai nilai, kesiapan SDM. Pemerintah harus memprakarsai kebijakan khusus diantaranya berupa kebijakan fiskal dan insentif untuk mengembangkan industri prioritas dan klaster industri perkapalan.